Study guides

Q: How do you do 3X squared plus 18 plus 9?

Write your answer...

Submit

Related questions

The given expression can be simplified to: 8x squared +9

9x2 - 6xy + y2 - 81 = (3x - y)2 - 81 = (3x - y - 9)*(3x - y + 9)

-27

Divide the entire equation by 9. (9x2 + 27x + 18)/9 would then be 9(x2 + 3x +2) The factors of this equation would be 9(x + 1)(x + 2)

9x2 - 6xy + y2 - 81 = (3x - y)2 - 92 = (3x - y - 9)(3x - y + 9)

(8x + 9)(3x^2 - 1)

27-9 =18. 18/3 =6

7(3y-2)-(-4y+9)

5x^2 + 6x + 9 + (?) = -x^2 +3x + 3 (?) = -5x^2 -6x - 9 -x^2 +3x + 3 = -6x^2 -3x -6 Ans: -6x squared +3x -6

(x - 6)(x + 9)

57

I got 441. -9 x 2 = -18. -18 - 3 = 21 21 x 21 = 441

4x+6-7x+9=18-3x+15=18-3x=3x=-1

27x2 - 90x + 27 = 9*(3x - 1)*(x - 3)

6 squared plus 9 squared is equal to 117.

Since the problem has 4 terms, first you factor x cubed plus 9x squared, then you factor 2x plus 18. So when you factor the first two term, you would get x sqaured (x plus 9). Then when you factor the last two terms and you get 2 (x plus 9). Ypure final answer would be (x squared plus 2)(x plus 9)

-51

1/3x + 6 = 9 Restating the problem x + 18 = 27 I multiplied by 3 x = 9 I subtracted 18 from 27

(5x 2 - 8x + 1) + (2x 2 - 4x - 11)

3x plus 9 equals what?

5x+18 = 2x+9 5x-2x = 9-18 3x = -9 x = -3 and y = 3

48x2+139+63 = (3x+7)(16x+9) when factored and worked out with the help of the quadratic equation formula

4x3+12x2+3x+9

The equivalent expression of 3x-9 plus 3x plus 5 is negative 4.

2x-1/9+x-1/6=3x+5/122x+x=3x 1/9-1/6=-1/183x-1/18=3x+5/12-3x........-3x-1/18=5/12+1/18 +1/18No Answer: 0≠17/36